2014
DOI: 10.1504/ijpp.2014.063081
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructural mechanisms leading toward pro-accountable care organisation orientation: a survey of hospital managers

Abstract: Organisations across the country are transforming the way they deliver care, in ways similar to the accountable care organisation (ACO) model supported by Medicare. ACOs modalities are varying in size, type, and financing structure. Little is known about how specific infrastructural mechanisms influence hospital managers’ pro-ACO orientation. Using an electronic-survey of hospital managers, this study explores how pro-ACO orientation, as a latent construct, is captured from the perceptions of hospital managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Finally, although there is some theoretical basis for relating the number of the health care provider’s network affiliations to a pro-ACO orientation, 7 we were not able to examine this association for the RHC respondents. We had posed a question on the number and nature of the respondent clinic’s network affiliations.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Finally, although there is some theoretical basis for relating the number of the health care provider’s network affiliations to a pro-ACO orientation, 7 we were not able to examine this association for the RHC respondents. We had posed a question on the number and nature of the respondent clinic’s network affiliations.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the number of network affiliations has been found to be positively and significantly related to pro-ACO orientation in a recent study of acute care hospitals. 7 Primary care organizations and hospitals located in rural areas may be delayed in joining ACOs or deterred from joining them altogether. Thus far, ACOs are more often located in urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Mackinney and colleagues 24 suggested that rural providers should use a network with a larger health care systems strategy to establish ACOs. Wan and colleagues 25 emphasize how organizations with a large health provider network size increase their likelihood of participating in an ACO. However, many RHCs are not familiar with ACOs as a new health care delivery model.…”
Section: Theoretical Foundation and Literature Reviewmentioning
confidence: 99%